Analisis Penyebab Kegagalan Mesin Wrapping Menggunakan Failure Mode And Effect Analysis di PT. X - Candrianto Candrianto; Rizaldi Sardani; Rizki Fadhillah Lubis; M. Zakaria (Politeknik ATI Padang, 2021)
PT. X is an industry that produces green tea and black tea. In this study, there are often problems with the wrapping machine due to the age of use and the tight schedule of usage in the wrapping machine. If the machine operates in an unstable condition, it will greatly affect the results of the production. Damaged components such as cutting blades, heating heaters, thermo control and bearings. By using the Failure Mode and Effect Analysis (FMEA) method and also calculating the Risk Priority Number (RPN) value, the highest RPN value to the lowest is obtained, namely Cutting Knife (RPN = 100), Heater (RPN = 90), Thermo Control (RPN = 72) and Bearings (RPN = 36). It can be seen that the cause of damage to the wrapping machine and also the highest RPN calculation is found in the damage to the cutting knife whose RPN value is 100. From the analysis of the damage to the cutting knife, the author provides a suggested repair plan for the company so that it can be implemented in the company which can later improve the quality of the machine to be operated. for the future which cannot be separated from the supervisory role of the operators in charge of their cooperation to improve quality and the quality control team that always monitors quality.